Brazen virtue - Roberts, Nora (D.C. Detectives., 2001)
Superstar mystery novelist Grace McCabe needs to unwind after a grueling book tour. Visiting her sister whom she hasn't seen in months, seems the perfect solution. Grace returns home one night to find her sister dead, strangled with the cord of her phone.